Efektivitas Kebijakan Harga Pembelian Gabah dan Beras oleh Pemerintah sebagai Instrumen Stabilisasi Harga di Pulau Lombok Nusa Tenggara Barat - Suparmin; Siddik, M; Zaini, Anas; Tajidan (Analisis Kebijakan Pertanian, 2023)
The main problem in the rice economy is how to keep the price of paddy at the producer (farmer) level not too low and the rice price at the consumer level not too high. The objectives of this study were 1) to analyze paddy price stability at the farmers’ level and the effect of the implementation of the Government Procurement Price (HPP) on paddy price received by farmers, 2) to analyze the causes of the price disparity and transmission between paddy and rice prices, and 3) to analyze the effectiveness of HPP policy on the paddy price stability. The data used were the secondary data of 2014-2019, gathered from the National Logistic Agency, Statistics Indonesia, and Regional Agriculture Office, all in West Nusa Tenggara Province. The methods of analysis used were coefficient of variation, simple linear regression, and multiple linear regression. The study’s result showed that the HPP policy’s impact on the paddy price stability of farmers’ level was relatively stable during the 2014 - 2019 period. Other findings were the disparity between the price of paddy and rice was caused by two factors, namely the dynamic price pattern and the flexibility of price transmission. In addition, the implementation of the HPP policy on paddy price stability was effective. The recommendation from this study is the government should strengthen the bargaining position of farmer groups by encouraging them to sell dried-milled paddy, provide adequate drying facilities, and continue and maintain effectivity of the HPP and related policies.